2011
DOI: 10.21236/ada553752
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Effects on the Incubation Time Characteristics in Stress-Corrosion Cracking

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions searching data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information Send comments regarding this burden estimate or any other aspect of this collection of information including suggestions for reducing this burden to Washington Headquarters Service, Directorate SPONSORING/MONITORING AGENCY NAME(S) AND ADD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…Owing to lack of any confirmatory or contradictory data, we assume that Chu et al's results are correct. Jiang et al [37] observed the same trend of Chu's results in his 7075-T651 alloy (in 1 pct NaCl solution) by applying single overloads in tension and in compression at a constant K = 10 MPa(m) 1/2 , to measure incubation times. They observed the incubation times to be shorter by a factor of 100 under compression underload (due to tensile residual stress) vs tension (due to compressive residual stress) overload, at the same applied load of ±100 MPa (Figure 16).…”
Section: Discussionsupporting
confidence: 61%
“…Owing to lack of any confirmatory or contradictory data, we assume that Chu et al's results are correct. Jiang et al [37] observed the same trend of Chu's results in his 7075-T651 alloy (in 1 pct NaCl solution) by applying single overloads in tension and in compression at a constant K = 10 MPa(m) 1/2 , to measure incubation times. They observed the incubation times to be shorter by a factor of 100 under compression underload (due to tensile residual stress) vs tension (due to compressive residual stress) overload, at the same applied load of ±100 MPa (Figure 16).…”
Section: Discussionsupporting
confidence: 61%